PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN CHAT GPT TERHADAP HASIL BELAJAR KOGNITIF SISWA DALAM PEMBELAJARAN IPAS SISWA SEKOLAH DASAR - Fenta Mayasari; Edi Kurniawan; Muh Sholeh; Indriana Eko Amaidi; Amin Yusuf; Sungkowo Edy Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by ChatGPT on students’ cognitive learning outcomes in IPAS learning at SD Negeri 184/III Pauh Tinggi. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 146 students, with class V A as the control group (16 students) and class V B as the experimental group (19 students), selected using purposive sampling technique. The research instrument was a cognitive learning outcome test that had been validated and tested for reliability. Data analysis was conducted through normality and homogeneity tests, followed by hypothesis testing using an independent sample t-test. The results showed a significant difference in cognitive learning outcomes between the experimental and control groups, with a significance value of less than 0.05. The average posttest score of the experimental group was higher than that of the control group. Therefore, it can be concluded that the Problem Based Learning model assisted by ChatGPT has a significant effect on improving students’ cognitive learning outcomes. This model is effective in creating active, interactive, and meaningful learning.